2023
DOI: 10.3390/toxics11020094
|View full text |Cite
|
Sign up to set email alerts
|

Short-Term Exposure Effect of Ambient Fine Particulate Matter, Ozone and Cold Temperature on Emergency Room Visits for Asthma Patients

Abstract: (1) Background: The acute effects of ozone, cold temperature and particulate matter less than 2.5 μm (PM2.5) in size related to asthma attacks are well known worldwide. The adverse effects of ozone and cold temperature on asthma morbidity in Taiwan are still inconclusive. (2) Methods: This retrospective study included patients who had asthma emergency room visits (ERVs) from 1 January 2016 to 31 December 2019 in a regional hospital in Taiwan. The short-term negative effects were estimated using Distributed Lag… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 36 publications
(45 reference statements)
1
5
0
Order By: Relevance
“…Our study found that 10.2% of pediatric asthma ERVs occurred alongside a 7.7 µg/m 3 PM 2.5 increase. A spike in the concentration of PM 2.5 was noted in a past study in Taoyuan due to the burning of Joss paper in April [9]. Our study revealed similar findings with the burning of Joss paper during the Qingming Festival in April, which resulted in a higher PM 2.5 concentration in the second quarter every year from 2016 to 2019.…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…Our study found that 10.2% of pediatric asthma ERVs occurred alongside a 7.7 µg/m 3 PM 2.5 increase. A spike in the concentration of PM 2.5 was noted in a past study in Taoyuan due to the burning of Joss paper in April [9]. Our study revealed similar findings with the burning of Joss paper during the Qingming Festival in April, which resulted in a higher PM 2.5 concentration in the second quarter every year from 2016 to 2019.…”
Section: Discussionsupporting
confidence: 88%
“…The lower air temperature mediated with higher PM 2.5 increased the severity of chronic obstructive pulmonary disease in cold weather [16]. A study revealed that short-term cold weather exposure (25% lower in a quarter) related to asthma ERVs at all ages was lower than that related to the mean ambient temperature, with an RR of 1.21 and a 1-day lag [9]. The minimum air temperature in the cold season causes 2.26% of asthma cases and stronger hazard effects for PM 2.5 and SO 2 in the cold season with a 1-day lag [38].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our results showed a mildly increasing trend in the mean ozone level, as compared with the decreasing trends of the other air pollutants ( Table 2 ). Possible reasons for the increase in ozone are the empowered photochemical reactions of increased global temperature [ 45 ], the development of the semiconductor industry [ 26 ], and the use of negative ion air purifiers and ozone machines for reducing pathogens during the COVID-19 pandemic in urban regions. The inverse effect showed the ozone levels and the number of ERVs exhibited a negative correlation in Korea [ 46 ].…”
Section: Discussionmentioning
confidence: 99%
“…To combat global ozone pollution, more aggressive reductions in fossil fuel consumption are needed to reduce NO, volatile organic compounds, and greenhouse gas emissions [ 24 ]. In Taoyuan, Taiwan, the RR of the ERVs for asthma after ozone exposure was 1.2 [ 26 ].…”
Section: Introductionmentioning
confidence: 99%